The filmmaker's eye the language of the lens : the power of lenses and the expressive cinematic image - Mercado, Gustavo (Routledge, 2019)
The Language of the Lens explores the expressive power of the camera lens and the storytelling contributions that this critical tool can make to a film project. This book offers a unique approach to learning how lenses can produce aesthetically and narratively compelling images in movies, through a close examination of the various ways lens techniques control the look of space, movement, focus, flares, distortion, and the "optical personality" of your story's visual landscape. Loaded with vivid examples from commercial, independent, and world cinema, The Language of the Lens presents dozens of insightful case studies examining their conceptual, narrative, and technical approaches to reveal how master filmmakers have harnessed the power of lenses to express the entire range of emotions, themes, tone, atmosphere, subtexts, moods, and abstract concepts. The Language of the Lens provides filmmakers, at any level or experience, with a wealth of knowledge to unleash the full expressive power of any lens at their disposal, whether they are shooting with state-of-the-art cinema lenses or a smartphone, and everything in between